Mia's golden bird / 2. - Schroeder, Lisa (Charmed life, 2014)
Mia hopes the good luck charm bracelet she and her friends from summer camp bought will help as she deals with the gossip of classmates as she photographs birds for her grandmother's friend--famous actress Lacy Bell.